2005
DOI: 10.1681/asn.2004070621
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Cascade Activation Causes CC Chemokine Receptor-2 Gene Expression and Mononuclear Cell Activation in Hemodialysis Patients

Abstract: Priming of the coagulation cascade during hemodialysis (HD) leads to the release of activated factor X (FXa). The binding of FXa to its specific receptors, effector protease receptor-1 (EPR-1) and protease-activated receptor-2 (PAR-2), may induce the activation of peripheral blood mononuclear cells (PBMC) and promote a chronic inflammatory state that is responsible for several HD-related morbidities. In the attempt to elucidate the mechanisms underlying the coagulation-associated inflammation in HD, 10 HD pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
0
19
1
Order By: Relevance
“…Furthermore, we have reported that dialysis modalities with high convective transport are capable of reducing but not normalizing the percentage of CD14 ϩ CD16 ϩ monocytes (13). During the HD process, the interaction of peripheral blood mononuclear cells with the dialysis membrane may activate the former, with consequent increased synthesis and release of proinflammatory cytokines (23,24). Our results may be partially explained by the greater ability of PD to remove high-molecular weight uremic toxins (25), although the potential role played by the contact between blood and foreign surfaces in the HD procedure should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have reported that dialysis modalities with high convective transport are capable of reducing but not normalizing the percentage of CD14 ϩ CD16 ϩ monocytes (13). During the HD process, the interaction of peripheral blood mononuclear cells with the dialysis membrane may activate the former, with consequent increased synthesis and release of proinflammatory cytokines (23,24). Our results may be partially explained by the greater ability of PD to remove high-molecular weight uremic toxins (25), although the potential role played by the contact between blood and foreign surfaces in the HD procedure should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo data suggest that cytokine production during HD is caused by (a) direct contact of leukocytes with dialysis membrane (Panichi et al, 2000;Pertosa et al, 1991), (b) active complement fragments generated during HD (Pertosa, Tarantino, Gesualdo, Montinaro, & Schena, 1993) and (c) back transport of bacterial derived material from the dialysate into the blood compartment (Bommer, Becker, & Urbaschek, 1996;Laude-Sharp et al, 1990). Complement activation during HD stimulates the transcription of cytokine genes, and a second stimulus with bacterial product facilitates the translation and secretion of cytokine proteins (Pertosa, Gesualdo, Bottalico, & Schena, 1995;Pertosa et al, 2005;Schindler, Lonnemann, Shaldon, Koch, & Dinarello, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the authors stated that heparin may act as a prooxidant agent increasing oxidative stress, but the use of unfractionated heparin has not been tested in this work (23). In a previous study, we demonstrated that subclinical clotting activation caused an increased CCR2 gene expression in uremic PBMCs; the use of EVAL improved this condition by reducing specific FXa and MCP-1 cell surface receptors (27). In this study we showed that patients treated with EVAL had significantly lower plasma levels of prothrombin F1 + 2, suggesting a low blood clotting activation.…”
Section: Discussionmentioning
confidence: 86%
“…Subclinical clotting activation contributes to HD-related chronic microinflammation, and thus the use of a less thrombogenic membrane, such as ethylene-vinyl-alcohol (EVAL), may improve this condition (27). EVAL is a synthetic polymer having both hydrophilic and hydrophobic segments.…”
Section: Introductionmentioning
confidence: 99%